Retrobulbar Hemodynamic Effects of Nipradilol in Normal and Normal-Tension Glaucoma Eyes - Mitsushi Fukukita; Masashi Ido; Syunsuke Osawa; Mikio Sasoh; Motoyasu Furuta; Kunio Ito; Masahiko Sugimoto; Yukitaka Uji (Journal of Ophthalmology)
Purpose. To investigate the effects of nipradilol on retrobulbar hemodynamics. Methods. We investigated normal and normal-tension glaucoma (NTG) eyes. Topical nipradilol (one eye) and placebo eye drops (fellow eye) were instilled for 1 week in volunteers. Nipradilol was also instilled in NTG patients. Ultrasound color Doppler imaging for the posterior vessels was performed before, 2 hr, 1 week (for normal), and at 4 weeks (for NTG). Results. In normal eyes, there were significant decreases in the resistance index (RI) for the temporal short posterior ciliary arteries (PCA) at 2 hr and for the ophthalmic arteries at 1 week. There were no significant changes in the placebo-treated eyes. In the NTG eyes, there was a significant decrease in the RI for the central retinal artery, nasal, and temporal PCA at 2 hr and 4 weeks. Conclusion. Short-term observations found that nipradilol increased the ocular blood flow in normal and NTG eyes.